Pengaruh E-Wom, E-Service Quality, dan Perceived Quality terhadap Purchase Intention pada Marketplace Tokopedia - Nugroho, Filipus Ismoyo Satriyo Dwi; Wahyuningsih, Tri Harsini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E- WOM), electronic service quality (E-Service Quality), and perceived quality on purchase intention among Tokopedia app users. A quantitative research method using a survey approach was employed, distributing questionnaires to 152 active Tokopedia app users in November 2024. The data was analysed using multiple linear regression to examine the relationships between variables. The results show that all three independent variables, namely e-wom, e- service quality, and perceived quality, have a positive and significant influence on purchase intention. These variables explain 77.2% of the changes in purchase intention, while the remaining 22.8% is explained by other factors outside the scope of this study. Managing e-wom, e-service quality, and consistently maintaining perceived quality is crucial for increasing consumers' purchase intention on the Tokopedia app.